Pengaruh Perawatan Punggung Terhadap Penurunan Tingkat Rasa Nyeri Punggung Bagian Bawah Pada Ibu Hamil Trimester III di Puskesmas Depok II - Chici Riansih (Jurnal Permata Indonesia, 2022)
Background: Back pain in pregnant women is pain or pain felt by the mother in the back area, which causes discomfort. This back pain can be reduced by back exercises. Low back pain is a complex pain complaint that most often occurs in third trimester pregnant women. It is estimated that about 70% of pregnant women complain of back pain during pregnancy. Objective: To determine the relationship between lower back pain levels in third trimester pregnant women at the Depok II Health Center. Methods: This type of research is a quantitative study with a cross sectional design. The population in this study were all pregnant women TM III Prenatal Class at the Depok II Health Center totaling 35 pregnant women. The sample technique in this study was total sampling. Data analysis using Spearman Rank. Results: the results showed that most of the pregnant exercisers experienced back pain before the exercise was carried out as many as 19 (54.3%). Meanwhile, after the pregnancy exercise, most of the mothers stated that they had moderate back pain 22 (65.9%). Spearman rank test results 0.000 < (0.05). Conclusion: there is an influence between back activity on decreasing the level of lower back pain in third trimester pregnant women at Depok II Health Center.